ASSESSING THE IMPACT OF SUBSTANCE ABUSE ON CONSTRUCTION PROJECTS IN JOS, NIGERIA - Sanda, Yakubu Nehemiah; Natalia A. Anigbogu; Rhibetnaan D. Panshak; Abdulganiyu Bello (Journal of Surveying, Construction and Property, 2023)
The use of drugs and other related substances in the construction industry is fast becoming a serious challenge. These substances when abused could have negative impact on the psyche of workers which affects the success of construction projects. This study therefore assesses the impact of substance abuse on construction projects with view to suggest possible measures for ameliorating those impacts towards successful project management. Questionnaire was used in collecting the data; mean score and charts were the instruments used in analysing the data. The major causes of substance abuse on construction sites were the stress of working long hours and pressure to meet up with strict deadlines. Substances commonly abused were locally brewed beer (burkutu), cannabis and prescription drugs such as emzol and tutoline. The rate of substance abuse among construction was adjudged to be high. Substance abuse affects workers’ ability to achieve project specifications, compromises clients’ satisfaction, causes cost and time overruns. The study suggests developing workplace drug and alcohol policies, pre-employment and random testing of workers and harsh punitive measures for offenders as effective strategies against substance abuse on construction sites in the study area.